Kekuatan Zikir dan Do’a Dalam Membina Aqidah Remaja di Desa Kolam Kecamatan Percut Sei Tuan - Junaidi Junaidi; Abdul Halim; Endang Ekowati (UIN Sumatera Utara, 2022)
Given the many negative behaviors that are carried out by teenagers in the village of Pool, especially the tradition of watching the kibot loading program that has existed for a long time, special handling is needed to save the younger generation, especially teenagers from this deviant tradition. Children are included in a group of people who are vulnerable and easily fall into negative things, because they usually give examples of what they see firsthand, especially in adolescence because of their unstable nature and have very high emotions. This change in social phenomena requires religious studies in order to strengthen the aqidah within a person. Religion is an option to overcome the problems that exist in humans. Therefore, researchers feel it is important to create a method of fostering aqidah in adolescents based on an Islamic perspective by doing remembrance and prayer together, as well as conducting Al-Qur'an therapy, remembrance therapy, and prayer therapy in response to conditions. adolescent social skills to improve spirituality (religion), morals (morals), and physical (physical). The purpose of this research is to find out the activities of the community of Pool Village in fostering the aqidah of teenagers, to find out the steps taken in fostering the aqidah of teenagers based on an Islamic perspective, and to determine the impact of remembrance and prayer activities in fostering the aqidah of teenagers in the Village of Pools. The methodology used in this research is through field research (Field Research) using a qualitative approach. The results of the research in the Pond Village, Percut Sei Tuan District, which focused on fostering the aqidah of teenagers with the method of remembrance and prayer together, found that the application of the proper creed of youth was certainly produced by proper research and observation. The activities of remembrance and prayer together in fostering the youth's aqidah are considered as a form of response to the social conditions of teenagers who are able to reduce the tradition of watching the kibot loading program, especially for adolescents in the range of 11-19 years who are considered very vulnerable to negative behaviors. The joint remembrance and prayer activities that were carried out received a positive response as a coaching medium that was considered capable of eliminating the disease of watching the kibot loading program which has become a tradition.